2012
DOI: 10.1111/j.1365-2559.2012.04200.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinicopathological study of malignant odontogenic tumours

Abstract: Malignant odontogenic tumours are considered rare central odontogenic lesions. Awareness of their existence, rapid diagnosis and successful treatment using surgery, radiation and/or chemotherapy is critical to patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
18
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 11 publications
8
18
1
6
Order By: Relevance
“…MOTs have been found to be difficult to specifically diagnose because of the variations in pathogenesis, histopathologic features, and biologic behavior, and the overall rarity of these diseases. 23 This study, to our knowledge, is the first to report survival data for both OS and DSS of MOTs, with a 5-year survival rate of 54% and 67%, respectively. Previous studies of specific odontogenic tumors have reported 5-year survival rates for OS alone to be 72.9% for ameloblastic carcinoma, 73% for odontogenic ghost cell carcinoma, and 30% for primary intraosseous carcinoma 30%.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…MOTs have been found to be difficult to specifically diagnose because of the variations in pathogenesis, histopathologic features, and biologic behavior, and the overall rarity of these diseases. 23 This study, to our knowledge, is the first to report survival data for both OS and DSS of MOTs, with a 5-year survival rate of 54% and 67%, respectively. Previous studies of specific odontogenic tumors have reported 5-year survival rates for OS alone to be 72.9% for ameloblastic carcinoma, 73% for odontogenic ghost cell carcinoma, and 30% for primary intraosseous carcinoma 30%.…”
Section: Discussionmentioning
confidence: 92%
“…This age at diagnosis, male predilection, and high frequency of presentation in the mandible is consistent with cases reported in the previous MOT literature. 7,10,23 Increased age at diagnosis was found to be associated with worse OS and DSS in univariate analysis and multivariate analysis of the overall cohort and stage I/II patients. Advanced age may decrease the rate of survival as a result of an age-dependent T-lymphocyte depletion, a higher propensity to development of metastatic disease, differences in management based on age, or an intolerance to the cytotoxic effects of chemotherapy.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…38,40,[72][73][74][75][76] Subsequently, the studies reporting inconsistent histologic diagnosis or those from which the clinicopathologic data retrieval was difficult were excluded. [58][59][60][61][62][63][64][65][66][67][68][69][70][71][73][74][75][76] Data on sociodemographic characteristics, clinical features, treatment, follow-up, and outcomes were collected and plotted for each study. Ultimately, this review resulted in 87 well-documented cases of CCOC retrieved from 53 articles.…”
Section: Immunohistochemical Datamentioning
confidence: 99%